SONGKET PANDAI SIKEK GAYA DAN FUNGSI - Desi Trisnawati; Ediantes Ediantes (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
Tenun songket Pandai Sikek has been known by the public ; tenun Pandai Sikek consists of balapak fabric (tenun fabric with full motif) and bacatua (tenun fabric witc spreadiang motif). The unigue characteristic of its weaving is the motif used namely Mnangkabau motif. Various creativities are done by the craftsmen so tenun Pandai Sikek is always preffered by the consumers. One of them is by packaging tenun songket pandai sikek into souvenirs and combining it with sulaman technique. The making of motif on the fabric of tenun songket pandai sikek is used to be done by pulling out the thread but nowadays the making of motif has been combined with sulaman technigue: the combination of tenun technigue and sulaman tecnigue is the newest innovation done by pandai sikek craftsmen, and its only found on the songket veil not on the other produkts. Motif applied with sulaman technigue is the stylization of the shape of rose and its parts such as leaf, suluak, stem, and flower bloom. There functions of art on tenun songket namely personal function is the craftsmens aesthetics channelled through the creation of songket that’s creative and innovative without limit; fusic function is the use value of a thing or product so it can be used as the ready-used tool and media that features the beauty value of that product; social function is related to personal collection, and desire to have something is the result of someones collection, and desire to have something is the result of someones collective nature. Tenun songket pandai sikek can be worn and used in formal events such as inauguration, gradution, marriage, and customary events in order to be more elegant and posh. Tenun songket pandai sikek tends to have classic and modern styles.